Design and Development of a Timing Chain-Based Washer Machine Prototype for Engine Valve Production - Prayuda, Ridzki; Abdillah, Hamid (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Engine valve is an important part of the valve mechanism system in an internal combustion engine that functions to regulate the flow in and out of the air and fuel mixture into the combustion chamber. The quality and clean efficiency of the valves contribute to optimal engine performance. The purpose of this study was to test the design of prototype engine washer engine valve timing chain-based by examining the comparison of cleaning quality and operating time efficiency with existing conventional engine washer valve. The method used in the study is the applied method. Data analysis obtained the time required for input 1 valve for 9 seconds, in the first experiment, 7 seconds in the second experiment, 6 seconds in the third experiment based on data taken valve position greatly affects the length of each valve to be input to the washing process. The test results show that the timing chain-based waher engine valve engine is able to reduce the time required with high accuracy. The cleaning process becomes more efficient and reduces the touch to the valve which makes the Valve have high quality. In addition, this engine valve waher engine reduces engine maintenance time, resulting in cost savings and improved overall efficiency.